Model Implementasi Metode Yanbu’a Berbasis Evaluasi Berjenjang Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Santri di Pesantren - M Mahbubi; Afifah Maulidah Hasanah (An-Nuha, 2026)
This study examines the implementation of the Yanbu’a method integrated with a tiered evaluation system to improve students’ Qur’anic reading skills in an Islamic boarding school. The research is motivated by the limited effectiveness of previous learning methods in developing accurate pronunciation, fluency, and mastery of tajwid rules among students. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and documentation involving 20 students, 3 teachers, and 1 program coordinator. The findings reveal that the Yanbu’a method, supported by structured level-based evaluation, significantly enhances students’ accuracy in makharijul huruf, reading fluency, and understanding of tajwid. Key instructional strategies such as musyafahah, individual recitation (sorogan), and repetition (takrir) contribute to these improvements. The study concludes that integrating systematic evaluation within the Yanbu’a method provides an effective model for ensuring quality control in Qur’anic learning.